Anti-cataract and anti-diabetic properties of Citrus hystrix dc. leaf extract in streptozotocin-induced diabetic rats - Umran, Nor Shahira Solehah (2019)
Citrus hystrix leaf is an important South-East Asian culinary ingredient with anti- oxidant, anti-inflammation, and cardio-protective properties. Inflammation, hyperglycaemia and oxidation are significant contributors to diabetic cataract formation. This study demonstrated the mitigating effects of Citrus hystrix leaf extract on diabetes and cataract development in female Sprague Dawley rats. Diabetes was induced by intraperitoneal streptozotocin (75 mg/kg) injection before the rats were orally administrated with the 150 and 300 mg of extract per kg body weight or metformin (250 mg/kg) for 8 weeks after diabetes development. The extract gradually a n d s i g n i f i c a n t l y decreased fasting blood glucose levels (p<0.05), reduced serum malondialdehyde (MDA), prostaglandin E2 (PGE2), vascular endothelial growth factor (VEGF), and tumor necrosis factor alpha (TNF-α) levels. Histological evidence showed the cataracts development were significantly suppressed by the 150 mg/kg extract (p<0.05), performing better than metformin, by ameliorating systemic inflammation (TNF-α, PGE2, VEGF), oxidative stress (malondialdehyde), hyperglycemia and lens- opacification. Good correlations were found between cataract incidence with fasting blood glucose (r²=0.90), serum PGE2 (r²=0.91), MDA (r²=0.99), VEGF (r²=0.71), and TNF-α levels (r²=0.49) suggesting these biomarkers may probably help predict cataract risk. The citrus compounds suppressed PGE2, VEGF, oxidation (MDA) and inflammation to probably prevent fluid influx, lens-fibers osmotic over-hydration, to mitigate diabetic cataract development. This study showed the limonoids and flavonoid rich Citrus hystrix leaf consumption, is a good anti-hyperglycemic/ anti-diabetic agent, with potent anti-oxidant and anti-inflammation properties that help preventing diabetic cataract development.